Pemanfaatan Bakteri Asam Laktat Indigenous Kopi Robusta sebagai Starter pada Fermentasi Kopi Arabika Asal Toraja - Sukmawati, Sukmawati; Patang, Patang; Sukainah, Andi (Agricultural Technology Education Study Program, 2024)
This research is in the form of an experimental study which has the aim of knowing the addition of indigenous lactic acid bacteria can have effect on the caffeine content of fermented arabica coffee. The reseach design used a completely randomized design which included 6 treatments with the addition of indigenous lactic acid bacteria, namely control treatment (0%), 1%, 2%, 3%, 4%, and 5% treatments for 48 hours of fermentation. Total plate count, pH, total acid titrated in fermented liquid, water content, ang caffeine content of coffee beans were all measured The ANOVA variance test with a signifikant level of α= 0,05 and the Duncan Multiple Range test (DMRT) further test were used in the data analysis. This study resulted that the concentration of indigenous lactic acid bacteria had an effect the total plate count, pH value of the fermented liquid, caffeine content of arabica coffee beans, but had no effect on total acid titrated on fermented liguid,water content of arabica coffee. The best treatment is the addition of 5% indigenous lactic acid bacteria which can reduce the caffeine content of coffee beans up to 1,47%.